Is neighbourhood destiny? Exploring the link between neighbourhood mobility and student outcomes. (February 2016) - Cordes, Sarah A; Schwartz, Amy Ellen; Stiefel, Leanna; Zabel, Jeffrey
The notion that children from 'good' neighbourhoods are destined for success while those from 'bad' neighbourhoods are destined for failure has considerable popular appeal. Residential location is strongly linked to school quality, access to educated adults, exposure to violence, etc. There is, however, surprisingly little evidence on the link between the neighbourhood in which a child begins school and later schooling outcomes. Understanding early neighbourhood experiences is important for determining whether students are 'stuck' in neighbourhoods of disadvantage. It is also critical for determining the extent to which students who begin their schooling careers in disadvantaged neighbourhoods are destined for poor schooling outcomes, and conversely, whether changing neighbourhood context improves student performance. In this study, therefore, we document how students' early neighbourhood and schooling experiences are related to later success in school, and explore how changing neighbourhood and school contexts explain differences in academic outcomes. Using data from New York City (NYC), we construct a panel containing all students enrolled as first graders in NYC public schools in 1996–1997, following them through academic years 2007–2008, which would be their 12th grade year if they made standard academic progress (annual one-grade promotion). Far from supporting the simplistic story of 'dead-end' neighbourhoods, our analyses describe a situation where students from poor neighbourhoods actually move more often than their peers in less disadvantaged neighbourhoods and are more likely to experience changes in neighbourhood and school quality, with 45.7% of neighbourhood moves from the poorest neighbourhoods being made to significantly higher quality neighbourhoods.